Perancangan Sistem Informasi Penjualan Produk Parfum Berbasis Web Pada Toko Rinas Mashel Bekasi - Raynaldy Mahdi Putra; Tesa Nur Padilah; Carudin Carudin (Jurnal Ilmiah Wahana Pendidikan, 2022)
Advances in Information Technology have experienced very significant developments in various aspects of human life, including in the electronic sales industry (E-Commerce). To take advantage of this potential, an E-Commerce Website-based Sales Information System is useful for selling goods or services through electronic media so that the process becomes computerized and able to function in processing data and changing data to obtain accurate information. Rinas Mashel is a store that sells a variety of inspired perfume products in Bekasi. In the process of making transactions, collecting data on goods and making reports at the Rinas Mashel store, they still use the manual method by recording them in a book, so this is considered very ineffective because it is feared that errors will occur due to human error factors. Therefore, the perfume product sales information system is needed by Rinas Mashel store to make it easier to run business processes and provide the information needed accurately. The results of this study are in the form of designing and implementing a sales system using the PHP, JavaScript, CSS, HTML programming languages with MySQL database. While taking advantage of this research is to be able to help Rinas Mashel to improve service by making it easier for customers in the sales transaction process and being able to help relieve admin performance in data collection and minimize errors in making sales reports.